Biografi Kepemimpinan Musa Dalam Kriteria: Karakter, Komitmen Dan Kompetensi - Yonatan, Eliya; Wahyuni, Sri (Jurnal Ragam Pengabdian, 2026)
In this study, researchers look at the important role of Moses in the history of the Old Testament Bible, as the author of the Pentateuch and wise leader. Through a descriptive-analytic approach, researchers look at the life and leadership of Moses in an educational context, with data from the Bible and related literature. Chosen by God to lead the Israelites out of Egypt, Moses showed extraordinary commitment through his challenging life journey. His steadfast character, strong commitment, and competence as a leader and educator provide an important legacy for Christian leaders in educating the younger generation. Moses' commitment to God's call, coupled with his competence in leading and teaching, is a role model for educational leaders. In the context of religious historical biography, Moses made a major contribution to the spiritual and cultural development of Israelite society. This study emphasizes the importance of character, commitment, and competence in Christian leadership, as well as the importance of paying attention to the example of Moses in forming quality leaders and educators